The reconstruction of Maternal Audit with the electronic health information System - Prita Muliarini (SOEPRA, 2019)
Abstract: the maternal audit Program that took place since 2012 as the development of quality improvement efforts and safety of maternal health services is still not by Hope. The maternal audit process itself is lengthy so that there can be certain time gaps in problem-solving, the possibility of changing the contents of the clinic's audit and a verbal autopsy is inaccurate. This research is expected to answer questions and provide solutions for the lack of functioning of the maternal audit in reducing maternal mortality, and generate a comprehensive policy in the effort to reduce maternal mortality by auditing Maternal quality.